An unusual presentation of a minor head injury sustained during a game of rugby. Issue 7 (20th June 2007) - Rimal, Debesh; Thapa, Sonu R; Munasinghe, Namal; Errington, Mark
Abstract : In the UK, about 2% of the population attend the accident and emergency (A&E) department every year after a head injury. A majority of the patients have minor head injury and are discharged. Studies reveal that patients who reattend the A&E after a minor head injury represent a high-risk group. Concussion injuries are common and not all require treatment at the time of presentation. However, some may worsen after initial presentation and develop signs of serious head injury. A case of minor head injury as a result of head butt during a game of rugby, not associated with alteration in conscious state or focal neurological signs, and subsequent development of frontal lobe abscess a month later is reported. It is important that patients fit to be discharged at the time of consultation are discharged in the care of a responsible adult with clear head injury instruction sheets and are advised to return should their symptoms change. A high index of suspicion should be maintained and an early imaging technique, such as CT scan should be considered in patients reattending the A&E with persistent symptoms even after minor head injury.